TECHNICAL DESIGN OF WELLS (SUMP) AND PUMP REQUIREMENTS IN OPEN PIT MINE DRAINAGE AT PT. MULIA BARATAMA PLAN, LONG BELEH, KEMBANG JANGGUT, KUTAI KARTANEGARA, EAST KALIMANTAN - Avellyn Shinthya Sari; Yudho Dwi Galih Cahyono; Yopi Kombongkila (Institut Teknologi Adhi Tama Surabaya, 2023)
PT. Rencana Mulia Baratama is one of the companies engaged in coal mining in Long Beleh Village. The area of WIUP OP owned is 3,993 ha with a Production Forest Area of 2,630.4. The drainage system applied at PT. Mulia Baratama's plan is Mine Dewatering, which is by flowing all runoff water into a well (sump) to be pumped out of the mining area which flows into the settling pond. The well is a place that serves to hold a temporary amount of water before being pumped out The actual volume of the well in pit 1 is 58,000 m3. The planned rainfall period based on the 5-year rain reset period is 179.473 mm/day and the duration of rain is 2.4 hours per day. So that the amount of rain intensity calculated by the monobe equation is 37.39 mm/hour. The total water discharge entering the mining site is 58,817,254 m3/day which comes from runoff water discharge of 13,260,552 m3/day and rainwater discharge of 45,556,704 m3/day. The pumping discharge carried out is 462.4 m3/hour using one type of centrifugal pump 200x150 using Rpm 150 so that the total water discharge that can be drained in a day is 7,398.4 m3/day.